International Standards for Tuberculosis Care (ISTC) and Patients’ Charter: New Advances in Tuberculosis Care - Bhandari, Ramjee (Health Prospect, 2018)
DOI: http://dx.doi.org/10.3126/hprospect.v10i0.5651 Health Prospect Vol.10 2011, pp.43-45